Epicardial Adipose Tissue and IL-13 Response to Myocardial Injury Drives Left Ventricular Remodeling After ST Elevation Myocardial Infarction - Parisi, Valentina; Cabaro, Serena; D’Esposito, Vittoria; Petraglia, Laura; Conte, Maddalena; Campana, Pasquale; Gerundo, Gerardo; Abitabile, Marianna; Tuccillo, Andrea; Accadia, Maria; Comentale, Giuseppe; Pilato, Emanuele; et al. (Frontiers in Physiology, 2020)
Introduction. Left ventricular (LV) remodelling after ST-segment elevation myocardial infarction (STEMI) is explained only in part by the infarct size, and the inter-patient variability may be ascribed to different inflammatory response to myocardial injury. Epicardial adipose tissue (EAT) is a source of inflammatory mediators which directly modulates the myocardium. EAT increase is associated to several cardiovascular diseases, however its response to myocardial injury is currently unknown. Among inflammatory mediators, IL-13 seems to play protective role in LV regeneration, but its variations after STEMI have not been described yet. Purpose. In the present study we analysed the association between infarct-related changes of EAT and IL-13 in post-STEMI LV remodelling. Methods. We enrolled 100 patients with STEMI undergoing primary angioplasty. At the enrolment (T0) and after 3 months (T1), we measured EAT thickness by echocardiography and circulating levels of IL-13 by ELISA. Results. At T1, the 60% of patients displayed increased EAT thickness (EAT>0). EAT was directly associated to LV end-diastolic volume (r=0.42; p=0.014), LV end-systolic volume (r=0.42; p=0.013) and worse LV ejection fraction (LVEF) at T1 (r=-0.44; p=0.0094), independently of the infarct size. In the overall population IL-13 levels significantly decreased at T1 (p=0.0002). The IL-13 was directly associated to LVEF (r=0.42; p=0.017) and inversely related to EAT (r=-0.51; p=0.022), thus suggesting a protective role for IL-13. Conclusions. The variability of STEMI-induced ‘inflammatory response’ may be associated to the post-infarct LV remodelling. EAT thickness and IL-13 levels could be novel prognostic markers in STEMI patients.